Preparation and Evaluation of Chloramphenicol as Thermosensitive Ocular in- situ Gel - K. Ali Allah, Ali; N. Abd-Al Hammid, Shaimaa (Iraqi Journal of Pharmaceutical Sciences, 2017)
The purpose of this study was to develop poloxamer-based in-situ gel of chloramphenicol aiming to increase bioavailability and prolong corneal contact time, controlling drug release, and enhancing ocular bioavailability. The in-situ gel was prepared using different concentrations of poloxamer 407 combined with hydroxypropyl methyl cellulose (HPMC) or carbapol 940 to achieve gelation temperature about physiological temperature and improve rheological behavior and gelling properties of poloxamer gel. The prepared formulations were evaluated for their appearance, pH, and sol-gel transition temperature. The formulations F2, F3, and F5 have a gelation temperature within the accepted range 35-370C and were evaluated for their isotonicity, rheological studies, ocular irritation test, sterility and release studies. The selected formulations (F2,F3, and F5) isotonic, pseudoplastic, non irritant, pass sterility test, and the in vitro release demonstrated a diffusion-erosion controlled release of chloramphenicol over a period of 4 hr., 6 hr., and 6 hr. respectively.Key words: Chloramphenicol, in-situ gel, ocular dosage form, poloxamer.